The Analysis Of Human Development Index In West Sumatera: Can It Replace GDP as a Welfare Proxy?” - Yollit Permata Sari (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2018)
Human development is a process of enlarging the choices of people which means that the main point of development of a country is human. The definition of human development basically includes a vast dimension of development which not only emphasizes on economic growth but also its human quality. This research is aimed to analyze how big the effect of poverty level, expenditure per capita and government expenditure in education and health on Human Development Index (HDI) in West Sumatera. Using panel data analysis, the result of this study indicates that that poverty has a negative and significant effect on human development index. Expenditure per capita has a positive and significant effect on human development index. Government expenditure in education has a positive and significant effect on Human development index and the last government expenditure on health has a positive and bot significant on influencing human development index in West Sumatera at the year of 2010-2014.